2020
DOI: 10.1523/jneurosci.2083-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Tonotopic Map Changes in Humans Are Larger in Hearing Loss Than in Additional Tinnitus

Abstract: Neural plasticity due to hearing loss results in tonotopic map changes. Several studies have suggested a relation between hearing loss-induced tonotopic reorganization and tinnitus. This large fMRI study on humans was intended to clarify the relations between hearing loss, tinnitus, and tonotopic reorganization. To determine the differential effect of hearing loss and tinnitus, both male and female participants with bilateral high-frequency hearing loss, with and without tinnitus, and a control group were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 56 publications
3
49
0
1
Order By: Relevance
“…In the meantime various studies have directly or indirectly supported the notion that tinnitus may be more associated with a reduced neural gain than an enhanced neural gain. This was shown through reduced and delayed late ABR wave V in subacute tinnitus groups ( 28 ), reduced sound-evoked BOLD fMRI activity in the auditory cortex ( 23 , 52 ), reduced functional connectivity observed during sound-evoked activity ( 39 , 53 ), reduced resting-state functional r-fcMRI connectivity between auditory-specific brain regions and fronto-striatal regions ( 23 , 54 ) and reductions in the selectivity of frequency tuning that start at the level of the medial geniculate body and continue in the auditory cortex in tinnitus groups ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime various studies have directly or indirectly supported the notion that tinnitus may be more associated with a reduced neural gain than an enhanced neural gain. This was shown through reduced and delayed late ABR wave V in subacute tinnitus groups ( 28 ), reduced sound-evoked BOLD fMRI activity in the auditory cortex ( 23 , 52 ), reduced functional connectivity observed during sound-evoked activity ( 39 , 53 ), reduced resting-state functional r-fcMRI connectivity between auditory-specific brain regions and fronto-striatal regions ( 23 , 54 ) and reductions in the selectivity of frequency tuning that start at the level of the medial geniculate body and continue in the auditory cortex in tinnitus groups ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear damage causes altered auditory processing along the auditory pathway (for review see e.g., GourĂ©vitch et al, 2014;Eggermont, 2017a). While sound-trauma related changes have been mostly described for auditory brain stem centers, compensatory and/or erroneous functional map plasticity in higher sensory brain areas, as for instance the auditory cortex have also been demonstrated (Resnik and Polley, 2017;Koops et al, 2020). Such maladaptive map plasticity has been proposed to underlie the development of tinnitus (Eggermont, 2003;Engineer et al, 2011), although this classical model of tinnitus development has been challenged by alternative models (Schaette and Kempter, 2006;Krauss et al, 2016;Miyakawa et al, 2019;Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the human AC, functional imaging showed tonotopic map reorganization as a necessity for chronic tinnitus (for review see Eggermont, 2006), however this concept has been questioned (Langers et al, 2012) and recently Koops et al (2020) showed that tinnitus alters the reorganization of AC caused by hearing loss. A functional reorganization of the AC was previously shown in presbycusis with an increased activation of the right AC in elderly subjects (Profant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%